Thermo-Mechanical Properties of Concrete Mortar with Cenosphere - Beddu S.; Basri N.A.N.; Itam Z.; Mohd Kamal N.L.; Manan T.S.; Che Muda Z.; Mohamad D.; Sivakumar N.; Agusril; Lee K.X. (Springer Science and Business Media Deutschland GmbH, 2025)
Materials used in modern constructions received attention from researchers and engineers recently due to their impact on climate change, power consumption and operational cost. The usage of recycled materials gives extra advantages towards environment. It was found that power plant produced various types of waste product that can be utilize in many applications. For instance, Cenosphere produced as waste product from power plant have ability promotes thermo-mechanical properties of mortar to certain extents. Synthetic fibers such as Polypropylene (PP) was added to increase mechanical properties of mortar as well as thermal value. The aim of this study is to evaluate the effect of cenosphere and PP fiber added to concrete mortar on its mechanical properties and thermal conductivity at different compositions (0, 5, 10, 15 and 20%). Five separate mixes were tested in this report. The findings for mechanical properties tests suggested that the usage of cenosphere as sand replacement has significantly reduce the mechanical strength as well as density of samples. Twenty percentage of cenosphere caused the compressive and tensile strength together with density reduced to lowest value which are 8.6MPa, 8.20MPa and 1416kg/m3, respectively, as compared to other percentages. This study also revealed that k value reduced as low as 0.62W/mK due to incorporation of cenospheres and mixtures. It can be concluded that higher percentage of cenosphere used in mortar samples, thermo-mechanical value decreases. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2024.